Hubungan Perokok Aktif Dan Pasif Terhadap Risiko Hipertensi Pada Remaja Laki – Laki Di Wilayah Pedesaan Kabupaten Buton Tengah : Cross Sectional Study - Nurbaiti, Nurbaiti (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: According to the 2023 Basic Health Survey (Riskesdas), 7.4% of adolescents aged 10–18 years were classified as active smokers, with a higher prevalence in rural areas. This study contributes scientifically by focusing its analysis on male adolescents in rural areas, as they constitute a high-risk population that is rarely the subject of research on hypertension risk factors.Methods: This study is an analytical observational study with a cross-sectional design, which aims to determine the relationship between exposure and disease incidence. The study sample totalled 78 respondents selected from a total population of 352 students. The sampling technique used was probability sampling with systematic random sampling method. Data analysis was conducted using non-parametric test, namely Spearman's rho test.Result: The results showed a Spearman correlation coefficient value of ρ = 0.567 (p = 0.000) in active smokers, while in passive smokers the correlation value was higher at ρ = 0.736 (p = 0.000). So that both active and passive smokers have a significant relationship with the incidence of hypertension. However, the correlation between passive smoking and hypertension is stronger than that of active smokers, indicating that indirect exposure to cigarette smoke also has a serious impact on the incidence of hypertension.Conclusion : Cigarette smoke exposure, particularly passive smoking in rural households, strongly correlates with adolescent hypertension, highlighting the need for targeted prevention and smoke-free policies involving families, schools, and policymakers.Keywords: Active smoking; Passive smoking; Adolescent males; Rural; Hypertension